The Roles of Inflammasomes in Host Defense against Mycobacterium tuberculosis - Ma, Jialu (Pathogens, 2021)
Mycobacterium tuberculosis (MTB) infection is characterized by granulomatous lung lesions and systemic inflammatory responses during active disease. Inflammasome activation is involved in regulation of inflammation. Inflammasomes are multiprotein complexes serving a platform for activation of caspase-1, which cleaves the proinflammatory cytokines such as interleukin-1β (IL-1β) and IL-18 into their active forms. These cytokines play an essential role in MTB control. MTB infection triggers activation of the nucleotide-binding domain, leucine-rich-repeat containing family, pyrin domain-containing 3 (NLRP3) and absent in melanoma 2 (AIM2) inflammasomes in vitro, but only AIM2 and apoptosis-associated speck-like protein containing a caspase-activation recruitment domain (ASC), rather than NLRP3 or caspase-1, favor host survival and restriction of mycobacterial replication in vivo. Interferons (IFNs) inhibits MTB-induced inflammasome activation and IL-1 signaling. In this review, we focus on activation and regulation of the NLRP3 and AIM2 inflammasomes after exposure to MTB, as well as the effect of inflammasome activation on host defense against the infection.